Basi‐parallel anatomical scanning–magnetic resonance imaging for the diagnosis of reversible cerebral vasoconstriction syndrome of the basilar artery: a case report. Issue 4 (28th July 2017) - Yamamoto, Akitaka; Omori, Yukinari; Shindo, Akihiro; Imai, Hiroshi; Suzuki, Hidenori
Abstract : Case: Reversible cerebral vasoconstriction syndrome (RCVS) is an increasingly recognized and important cause of thunderclap headache. Delays in diagnosis may cause deterioration of symptoms and concomitant unnecessary investigations. However, the diagnosis of RCVS in the acute stage remains difficult. A 41‐year‐old man was admitted to the emergency department for severe, recurrent occipital headaches. The results of initial computed tomography and magnetic resonance imaging (MRI) of the brain and cerebrospinal fluid analysis were normal. Magnetic resonance angiography (MRA) showed multisegmental luminal stenosis of the basilar artery. Basi‐parallel anatomical scanning (BPAS)‐MRI, illustrating the outer contour of the vertebrobasilar artery, also showed multisegmental stenosis. Outcome: The patient was speculated as having RCVS and was treated with oral lomerizine hydrochloride. Repeat MRA and BPAS‐MRI 2 months later showed resolution, confirming RCVS. Conclusion: Combined with MRA, BPAS‐MRI is an effective and non‐invasive imaging method for diagnosis of RCVS of the basilar artery. Abstract : Early and accurate diagnosis of RCVS is of utmost important for appropriate management and prognosis. BPAS‐MRI may have a supplementary role to MRA in the diagnosis of RCVS of the basilar artery.